The Multiple Launch Rocket System (MLRS) Interactive Learning Program Integrationwith MySQL Database Integration for Data Storage - Nathong, Gunthorn; Kraikhow, Jedsada; Khantong, Ranchida; Maleecharoen, Piyariose; Santironnarong, Siraphob; Channum, Naris (Defence Technology Academic Journal, 2024)
One of Interactive learning method essential feature is to allow a customization in learning contents that best suited trainee thus maximizing the training effectiveness. Multiple Launch Rocket System (MLRS) interactive learning tool called D11A-Computer Based Training (D11A-CBT) was created on this principle. This program uses Unity to create an interface that allows communication of data between the program and DBMS. Thus, a large quantity of data, such as text, image, and video, can be organized, altered, and requested conveniently with no repercussion on the program. These data consist of the user account type, detailed description of MLRS components and logbook of the user. Users can select an appropriate account type such as visitor, trainer or trainee. Each account type will have different access to corresponding data that is deemed suitable. In addition, this interactive learning program can be installed on various platforms. This feature allows trainees to access training resources at any place and time thus improving their training performance. Furthermore, D11A-CBT program demonstrates the ability to modify and display updated data to the user in real time.